Accounting for Cambridge International AS & A level - Austen, David [et al.] (Oxford Oxford University Press, 2015)
Support exam potential, and lay the foundations for students' future careers. Written to match the latest Cambridge syllabus (9706), this resource covers all the key concepts, provides up-to-date case studies, and offers targeted exam practice to build confidence.
Include Index and Table
Keywords: Accounting--Examinations -- Accounting -- Examinations -- Study guides